Prevalence and correlates of depressive symptoms, and points of intervention, in rural central Uganda: results from a cross-sectional population-based survey of women and men - Seth C Kalichman; Susan M Kiene; Chii-Dean Lin; Katelyn M Sileo; Rhoda K Wanyenze; Katherine Schmarje Crockett; Rose Naigino; Michael Ediau; Haruna Lule; Nicolas Menzies; Moses H Bateganya (BMJ Open, 2022)
Objectives The present study aimed to identify the prevalence and correlates of depressive symptoms and potential intervention points among women and men from a population-based sample in rural central Uganda.Design A cross-sectional study.Setting Four districts in rural Uganda.Participants Women and men aged 15–59 residing in four districts in rural Uganda accepting home-based HIV testing who completed a baseline survey at the time of testing.Primary outcome measures Depressive symptoms measured by the 10-item Center for Epidemiological Studies Depression Scale using a cut-off score of 13 for significant depressive symptoms.Results Among a sample of 9609 women and 6059 men, 1415 (14.7%) women and 727 (12.0%) men met criteria for significant depressive symptoms. Having ever received mental health services was associated with lower odds of significant depressive symptoms (women: adjusted OR (adjOR)=0.32, 95% CI=0.22 to 0.47; men: adjOR=0.36, 95% CI=0.18 to 0.62). Having received outpatient (women: adjOR=3.64, 95% CI=3.14 to 4.22; men: adjOR=3.37, 95% CI=2.78 to 4.07) or inpatient (women: adjOR=5.44, 95% CI=4.24 to 6.97; men: adjOR=3.42, 95% CI=2.21 to 5.28) care in the prior 6 months was associated with greater odds of significant depressive symptoms. For women only, known HIV positive status (adjOR=1.37, 95% CI=1.05 to 1.77), and for men only, alcohol misuse (adjOR=1.38, 95% CI=1.12 to 1.70), were associated with increased odds of significant depressive symptoms.Conclusion Our findings suggest that depression screening within outpatient and inpatient settings may help to identify people in need of mental health services. Routine screening in outpatient or inpatient clinics along with the implementation of evidence-based interventions could ultimately help close the mental health gap for depression in this and similar settings.